Koalisi Partai Politik di Kabinet: Antara Penguatan Lembaga Kepresidenan atau Politik Balas Budi - Adi Syaputra, Muhammad Yusrizal (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The political party's position as a determinant of government head nomination in Indonesia made the political party a central and strong role in the determination of the Cabinet in the presidential government of Indonesia and allowed the political party to determine the Cabinet domination established by the President elected. This research aims to determine the model of the presidential institution strengthening in the multi-party era in Indonesia and to know the political and juridical construction of the presidential institution in determining the cabinet in Indonesia. The method used is a normative legal research method with a conceptual approach. The results of this research are, firstly that the strengthening of the presidential institution in the multi-party era can occur when done with the restriction of political parties through the mechanism of the parliamentary threshold. Secondly, that the political construction of the cabinet determination by the President is based on the coalition of political party supporters of the government, and the juridical construction of the President may elect the Minister of the party proposal because it is based on article 6A paragraph (2) The Constitution of the Republic of Indonesia 1945. Kedudukan partai politik sebagai penentu pencalonan kepala pemerintahan di Indonesia menjadikan Partai Politik memiliki peran sentral dan kuat dalam penentuan kabinet di Pemerintahan Presidentiil Indonesia dan memungkinkan partai politik untuk menentukan dominasi kabinet yang dibentuk oleh Presiden terpilih. Penelitian ini bertujuan untuk mengetahui model penguatan lembaga kepresidenan pada era multi partai di Indonesia, dan untuk mengetahui konstruksi politis dan yuridis lembaga kepresidenan dalam menentukan kabinet di Indonesia. Metode yang digunakan adalah metode penelitian hukum normatif dengan pendekatan konseptual. Hasil penelitian memperlihatkan bahwa pertama, penguatan lembaga kepresidenan di era multi partai dapat terjadi apabila dilakukan dengan pembatasan partai politik melalui mekanisme parlementary threshold. Kedua, bahwa konstruksi politis penentuan kabinet oleh presiden didasarkan atas koalisi partai politik pendukung pemerintahan, dan konstruksi yuridis presiden dapat memilih menteri dari usulan partai karena didasarkan pada Pasal 6A ayat (2) UUD 1945.